2011
DOI: 10.1002/jmri.22584
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and reproducibility study of four tractography algorithms used in clinical routine

Abstract: Purpose: To evaluate fiber tracking strategy in terms of acquisition schemes in conjunction with four algorithms used in clinical routine, we studied one of the major tracts, anatomically well known, and which should be preserved as much as possible during neurosurgery: the corticospinal tract. Materials and Methods:Two identical exams, composed of three DTI acquisition schemes (6, 15, and 32 gradient directions), were performed on 12 healthy subjects during two different sessions. For each subject, intra-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Nonetheless, this improvement has not yet been rigorously examined. Although several tractography evaluation studies have been conducted [2931], they examined the overall tracking results, which can also be affected by the applied reconstruction methods and tractography algorithms. A study specifically comparing voxel-based and ODF-based index is yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this improvement has not yet been rigorously examined. Although several tractography evaluation studies have been conducted [2931], they examined the overall tracking results, which can also be affected by the applied reconstruction methods and tractography algorithms. A study specifically comparing voxel-based and ODF-based index is yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…A previous probabilistic tractography study reported improved sensitivity comparing 12 to 60 directions data within the same subjects to examine major fibre pathways [76]. Tensaouti et al [77] also reported a significant increase in corticospinal tract volume between 6 and 32 diffusion-encoding direction data, but only a small volume increase between 15 and 32 direction data. In our study, 25 directions seemed to be sufficient for defining tracts between most of the seeds and targets.…”
Section: Discussionmentioning
confidence: 97%
“…Fiber tracking can be performed with different algorithms divided in two main categories: deterministic and probabilistic (Jones, 2008, 2010a; Descoteaux et al, 2009; Chung et al, 2011; Fillard et al, 2011; Tensaouti et al, 2011; Tournier et al, 2011). Deterministic tractography aims to model the data and, in practical terms, can be thought of as generating/reconstructing one fiber from each seed.…”
Section: Processing and Visualizationmentioning
confidence: 99%